Ciliary Assembly/Disassembly Assay in Non-transformed Cell Lines - Masaki Saito; Kensuke Sakaji; Wataru Otsu; Ching-Hwa Sung (Bio-Protocol, 2018)
The primary cilium is a non-motile sensory organelle whose assembly and disassembly are closely associated with cell cycle progression. The primary cilium is elongated from the basal body in quiescent cells and is resorbed as the cells re-enter the cell cycle. Dysregulation of ciliary dynamics has been linked with ciliopathies and other human diseases. The in vitro serum-stimulated ciliary assembly/disassembly assay has gained popularity in addressing the functions of the protein-of-interest in ciliary dynamics. Here, we describe a well-tested protocol for transfecting human retinal pigment epithelial cells (RPE-1) and performing ciliary assembly/disassembly assays on the transfected cells.